POLA PENDIDIKAN BAGI ANAK-ANAK PENYANDANG CACAT MENTAL (Studi di SLB Dharma Bakti Kelurahan Beringin Raya, Kecamatan Kemiling, Kota Bandar Lampung) - Anas, Martha; Fatimaningsih, Endry (JURNAL SOSIOLOGI, 2013)
The purpose of this research is to explain the pattern of education for children with mental disabilities in an unusual school, SLB Dharma Dharma Bakti Pertiwi, Beringin Raya, Kemiling Sub-district, Bandar Lampung. This study is qualitative research. The techniques of collecting data are interview and documentation, while the technique of data analysis is qualitative analysis. The conclusions of this study are: (1) The pattern of inclusive education implemented is regular or general education for children with special needs using a school-based curriculum or KTSP. The strategies used in the approach to the students are: Â students are considered as friends, being patient and individual. Instructional media used are textbooks, pictures and props as well as tools and materials for skill practice; (2) The special pattern of education for SLB students are general subjects by providing general subjects with verbal and nonverbal language or giving examples and demonstrations. Skill education and self fostering are given in order that the students will have special skills to take care of themselves and not depend on others. Education of language speaking skills is carried out empathically and by giving motivation to the students to follow the learning activities well, to be able to communicate with friends, teachers, parents and people around him;Â  (3) The level of absorption of the material with the students of SLB Dharma Dharma Bakti Pertiwi is adapted to the studentsâ ability. If the students do not understand and comprehend the material presented, the teacher will repeat until the students know and understand.